Warming offsets the benefits of elevated CO2 in water relations while amplifies elevated CO2-induced reduction in forage nutritional value in the C4 grass Megathyrsus maximus - Habermann, Eduardo; Dias de Oliveira, Eduardo Augusto; Contin, Daniele Ribeiro; Costa, João Vitor Campos Pinho; Costa, Katia Aparecida de Pinho; Martinez, Carlos Alberto (Frontiers in Plant Science, 2022)
Tropical grasslands are very important to global carbon and water cycles. C4 plants have increased heat tolerance and a CO2 concentrating mechanism that often reduces responses to elevated concentrations of CO2 ([CO2]). Despite the importance of tropical grasslands, there is a scarcity of studies that elucidate how managed tropical grasslands will be affected by elevated [CO2] and warming. In our study, we used a combination of a temperature-free air-controlled enhancement (T-FACE) and a free-air carbon dioxide enrichment (FACE) systems to increase canopy temperature and [CO2] under field conditions, respectively. We warmed a field-grown pasture dominated by the C4 tropical forage grass Megathyrsus maximus by 2°C above ambient under two levels of [CO2] (ambient (aC) and elevated (eC - 600 ppm) to investigate how these two factors isolated or combined regulate water relations through stomatal regulation, and how this combination affects PSII functioning, biochemistry, forage nutritive value, and digestibility. We demonstrated that the effects of warming negated the effects of eC in plant transpiration, water potential, proline content, and soil moisture conservation, resulting in warming canceling the eCO2-induced improvement in these parameters. Furthermore, there were additive effects between eC and warming for chlorophyll fluorescence parameters and aboveground nutritive value. Warming sharply intensified the eCO2-induced decrease in crude protein content and increases in forage fibrous fraction and lignin, resulting in a smaller forage digestibility under a warmer CO2-enriched atmosphere. Our results highlight the importance of multifactorial studies when investigating global change impacts on managed ecosystems and the potential consequences for the global carbon cycle like amplification in methane emissions by ruminants and feeding a positive climate feedback system.